Synthesis, reactions and biological evaluation of benzyltriazolophthalazine derivatives - El-Wahab, Ashraf Hassan Fekry Abd; Mohamed, Hany Mostafa; El-Agrody, Ahmed Mohamed; El-Nassag, Mohamed Ahmed; Bedair, Ahmed Hammam (European Journal of Chemistry, 2013)
A series of triazolophthalazine derivatives (4-22) were synthesized and characterized. The structures of the newly synthesized compounds were confirmed by spectral data. The newly synthesized compounds were also screened for their antimicrobial activity.